Inactivation of Escherichia coli ATCC 25922 and Saccharomyces cerevisiae IMR-R-L 962 in grapefruit [Citrus paradisi (Macf.)] juice by UV-C light: changes in bioactive compounds and quality characteristics - La Cava, Enzo Luciano (2018)
Fil: La Cava, Enzo Luciano. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.